The status system and social organization of Satsuma. A transl. of the Shumon Tefuda Aratame Jomoku. Analyzed and transl. by Torao Haraguchi, R.K. Sakai a.o. With an introd. by R.K. Sakai (University of Tokyo Press, 1975)
English and Japanese text.